Curriculum and Physical Education: some relationships with/about the body (Research, Society and Development, 2020)
The aim of this paper is to discuss the relationship between body, curriculum and physical education, through a theoretical reflection. For that, different bibliographic sources were used to think about the relationships between these three categories. It is worth noting that the establishment of these relationships was only possible due to the scope and complexity with which the concept of curriculum - and body - is assumed here. To this end, the article is organized into four sections: 1) Initial outlines; 2) Body and Physical Education: reflections from the curriculum; 3) Physical Education as a way of producing bodies; and, 4) Final considerations. The reflections presented in the context of the relationships between body, curriculum and physical education demonstrated how these three aspects are interwoven, are constantly being constructed and reconstructed, depending on the socio-cultural context in which one lives. Physical Education, a field of knowledge, a pedagogical practice permeated by the body, as an object of study and knowledge, has at school and in educational spaces-times the curriculum as a means of producing discourses and subjectivities. It is concluded that reflecting on the curricular and pedagogical practices, especially in / of Physical Education, allows us to think about the understanding of the body [and the subject] in modern and contemporary society.